2015
DOI: 10.1021/acsami.5b04704
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Defect Sites in Graphene with RuO2 for High Capacitive Performance

Abstract: Graphene is an attractive material for its physicochemical properties, but for many applications only chemically synthesized forms such as graphene oxide (GO) and reduced graphene oxide (rGO) can be produced in sufficient amounts. If considered as electrode material, the intrinsic defects of GO or rGO may have negative influence on the conductivity and electrochemical properties. Such defects are commonly oxidized sites that offer the possibility to be functionalized with other materials in order to improve pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…The rGO-RuO 2 material showed a specific capacitance of 1132 F g À1 at a scan rate of 50 mV s À1 . 87 Other studies proposed the combination of graphene with Fe 2 O 3 , 88 95 In situ anodic electropolymerization (AEP) was used by Wang et al to prepare polyaniline/graphene composite paper (GPCP) material which showed a specific capacitance of 233 F g À1 at a scan rate of 2 mV s À1 (Fig. 9).…”
Section: Capacitance Of Graphenementioning
confidence: 99%
“…The rGO-RuO 2 material showed a specific capacitance of 1132 F g À1 at a scan rate of 50 mV s À1 . 87 Other studies proposed the combination of graphene with Fe 2 O 3 , 88 95 In situ anodic electropolymerization (AEP) was used by Wang et al to prepare polyaniline/graphene composite paper (GPCP) material which showed a specific capacitance of 233 F g À1 at a scan rate of 2 mV s À1 (Fig. 9).…”
Section: Capacitance Of Graphenementioning
confidence: 99%
“…We determined no considerable change in the Raman spectra of the NWD electrode Adv. [56] Compared with the NOD electrode, the NWD electrode possessed higher crystallinity, viz., fewer defects, and thus demonstrating higher electrochemical stability. 2017, 7, 1602210 www.advenergymat.de www.advancedsciencenews.com after the reaction (Figure 7c).…”
Section: Resultsmentioning
confidence: 99%
“…Upon thermal annealing, the presence of C− −O− −C groups has also been reported. [41][42][43][44][45][46][47] It is important to realize that there are very few defects expected to be available on a freshly prepared HOPG surface and thus additional defects can be introduced intentionally by ion sputtering followed by annealing in oxygen. The chemical nature of both types of defects is expected to be similar based on the detailed previous studies; [48][49][50] however, the amount can be varied by varying the surface preparation conditions.…”
Section: Resultsmentioning
confidence: 99%